(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Fluorescent protein has been applied in various diagnostic and biotechnology application. However, in these applications, the temperature conditions are simulated at higher temperatures of 289K and 300K compared to natural sea anemone Cribrinopsis japonica fluorescent protein. This study evaluates the predictive structure and the molecular dynamic interaction of the protein with its target in different external temperature using ab initio similarity modeling and GROMACS/VMD respectively. Three-dimensional structure of the protein, named cjFP510 were predicted and analysed based on the highest similarity template model of Anemonia sulcata (2c9i) at 66.97%. The predicted model shows alternating a and β helices with longer loops and extra a-helix. cjFP510 was programmed with molecular dynamic simulation with template protein 2c9i as a reference to study its comparative adaptability in two different temperatures of 289K and 300K. cjFP510 was found to be more stable at both temperatures compared to 2c9i. Further simulation was conducted on the gyration radius to evaluate the compactness of the protein folding. Lower gyration radius of cjFP510 denotes more stable protein at 289K simulated environment than 29ci. This may be due to the presence of an extra a -helix based on the predicted model and few amino acid residues such as glycine, lysine, and arginine which contributed to the protein flexibility and thermal stability Conclusively, cjFP510 is more thermostable in the two conditional temperatures tested.